Synthesis, in-vitro bioactivity evaluation and molecular docking of monosaccharide ester and fatty acid amide derivatives of 5-aminosalicylic acid - Yousefi, Samira (2016)
5-aminosalicylic acid (5-ASA), structurally related to the salicylates, is active in the treatment of inflammatory bowel disease (IBD). Since IBD is a high-incidence disease and considering that 5-ASA has been approved as one of the most effective and tolerable drug for the majority of patients in treatment of IBD, up to date, varied derivatives with slightly different formulation of 5-ASA have been prepared to allow it to reach different areas of the bowel and to help keep the condition in remission. On the other hand, according to the documentary evidences on the remarkable properties of fatty acids and saccharides in various areas especially in pharmaceutical field, they have been proposed as beneficial candidates for conjugating with drugs in order to enhance drugs’ bioavailability. Therefore, in this work, a series of new monosaccharide selective ester derivatives of 5-ASA including galactose, fructose, glucose and xylitol esters and new fatty acid amide derivatives of 5-ASA including lauric, linoleic and oleic amide, were synthesized to study their anti-bacterial, anti-inflammatory and cytotoxicity activities in comparison with initial drug. The structures of all the produced compounds (sixteen compounds: including eleven unknown compounds and five known intermediates) were confirmed by spectroscopic methods (1H NMR, 13C NMR, IR and DIMS). Following that, the above-mentioned in vitro bioactivity evaluation was performed for all new final ester and amide derivatives of 5-ASA (four monosaccharide ester and three fatty acid amide derivatives). The antibacterial activity evaluation of them against Gram-negative bacteria and Gram-positive bacteria revealed that all were more effective against Gram-negative as well as Gram-positive bacteria than the parent drug (5-ASA) which showed insignificant activity. Furthermore, they were confirmed by the cytotoxicity assay over HT-29 and 3T3 cell lines to be less toxic for normal cells (3T3 cells) compared to the parent drug. On the other hand, however, their suppressive effect against colon cancerous cells (HT-29 cells) was somewhat lower. Meanwhile, the anti-inflammatory assay over RAW264.7 macrophage cell line demonstrated NO (nitric oxide) inhibition activity of these new derivatives of 5-ASA, moderately has improved in comparison with the parent drug. Although the mechanism of action of 5-ASA is still is unknown, but the clinical effectiveness of 5-ASA attributed to its inhibition effect on cyclooxygenase (COX-1/COX-2) and lipoxygenase (5-LOX) enzymes’ pathways which are playing a vital role in the inflammation process to produce inflammatory mediators. To predict the possible interactions and binding energy of the new compounds against these proteins, in-silico screening via molecular docking technique was performed and the new products exhibited greater hydrogen bonding and greater binding affinities with the active sites of proteins towards 5-ASA. As conclusion, eleven new monosaccharie ester and fatty acid amide derivatives of 5-ASA were synthesized successfully in average yields and showed approximately moderate to superior bioactivities for above-mentioned assays than 5-ASA which may help for drug development in future. Also, molecular docking was performed against two enzymes involved in the inflammation process to predict the possible interactions and binding energy of the new compounds for future in-vivo experimental works.